1954
DOI: 10.1039/tf9545001331
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasonics on the explosive sensitivity of ammonium permanganate

Abstract: Phenomena of thermal and ultrasonic initiation of solid explosives are briefly reviewed. In this work we have studied the explosive decomposition of ammonium permanganate when subjected to the action of ultrasonic radiation of constant frequency (2 mc). We found that ammonium permanganate crystals could not be exploded by the sound field in air alone, but had to be suspended in mineral oil. We also found that, as for thermal explosions, there is an induction period, the length of which depends on the intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…61 Silver fulminate has found some use as a primary explosive in naval weapons applications. 62 In addition, related molecular nonmetal oxides such as iodinanes, 63−65 xenon oxides, 66 and high-oxidation-state metal oxides such as chromates 67 and permanganates 68 , 9) is synthesized by the acidcatalyzed nitration of the sugar alcohol, glycerol (Scheme 4). 69 In comparison with black powder, nitroglycerine incorporates the oxidant (nitro group) directly into the organic fuel via covalent bonding which results in much faster reaction rates.…”
Section: N 0 -And N 1 -Based Energetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Silver fulminate has found some use as a primary explosive in naval weapons applications. 62 In addition, related molecular nonmetal oxides such as iodinanes, 63−65 xenon oxides, 66 and high-oxidation-state metal oxides such as chromates 67 and permanganates 68 , 9) is synthesized by the acidcatalyzed nitration of the sugar alcohol, glycerol (Scheme 4). 69 In comparison with black powder, nitroglycerine incorporates the oxidant (nitro group) directly into the organic fuel via covalent bonding which results in much faster reaction rates.…”
Section: N 0 -And N 1 -Based Energetic Materialsmentioning
confidence: 99%
“…Silver fulminate has found some use as a primary explosive in naval weapons applications . In addition, related molecular nonmetal oxides such as iodinanes, xenon oxides, and high-oxidation-state metal oxides such as chromates and permanganates can form dangerous explosive mixtures with fuels.…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Loginov et al [41] showed explosives such as RDX and lead azide were driven to initiation by applying low frequency mechanical vibrations. Theoretically, these techniques could be utilized as stand-off detection methods if, for example, heating of the target explosive could be achieved via an external source, such as ultrasonic radiation [43,44]. Despite this potential, only a few researchers have investigated these properties thoroughly.…”
Section: Thermal Characterization Of Explosives-thermal and Mechanica...mentioning
confidence: 99%
“…Nonthermal effects are certainly present during induction periods which may run for minutes (11,53). This must be so especially since, for some primary explosives at least, induction periods can be broken up into two or more stages separated by long intermissions (hours and even days so that the possibility of accumulation of heat is completely out of the question), and yet discontinuous periods of heating are essentially additive, their sum approximating the one-stage induction period (61,125). A theoretical analysis of such presensilization or memory effects has been given recently by Hess and Ling (67).…”
Section: Adiabatic Kineticsmentioning
confidence: 99%